Effect of Citronella Nano Biopesticide Against Mosaic Virus and Its Vector on Patchouli - Rita Noveriza; Maya Mariana; Tri Lestari Mardiningsih; Sri Yuliani (Buletin Penelitian Tanaman Rempah dan Obat, 2019)
The mosaic disease declines production and oil quality of patchouli. Antiviral-based citronella oil has been formulated using a spontaneous emulsification technique (nanotechnology). The previous result of the greenhouse trial showed the formula at 1-1.5 % concentrations suppressed the development of virus of about 82.5 %. The field-scale tests is necessary to be performed to validate the effectiveness of citronella nano biopesticide (CNB) against the mosaic virus and its vector on patchouli. The study was conducted in patchouli plantation at two locations (Pandeglang, Banten and Manoko, West Java). The research was arranged in a Randomized Completed Block Design (RCBD) with 6 treatments and 10 replications, each replication consisted of 50 plants. The treatments were formula of CNB at the concentration of (1) 0.5 %,   (2) 1 %, (3) 1.5 %, (4) 2 %, (5) insecticide (deltamethrin 0.2 %), and (6) control. The results showed that CNB formula at 1 % concentration with a monthly application effectively suppressed the development of mosaic disease in patchouli plants, and at 2 % concentration to control rolled-leaf aphid. The lowest intensity of mosaic disease (at 1 % concentration) was in Banten (23.12 %) and in West Java (18.35 %), while in control ranged from 26.31-44.94 % (Banten) and 19.60-23.12 % (West Java). Efficacy Index (EI) in Banten ranged from 12.12-48.55 % and in West Java was 6.38-20.63 %. The lowest intensity of aphid attack was showed by insecticide and CNB at 2 % concentration. The EI of CNB was 35.33 % (Banten) and 51.71 % (West Java) respectively.